The circadian oscillator gene GIGANTEA mediates a long-term response of the Arabidopsis thaliana circadian clock to sucrose - Dalchau, Neil; Baek, Seong Jin; Briggs, Helen M; Robertson, Fiona C; Dodd, Antony N; Gardner, Michael J; Stancombe, Matthew A; Haydon, Michael J; Stan, Guy-Bart; Goncalves, Jorge M; Webb, Alex AR (Proceedings of the National Academy of Sciences, 2011)
Circadian clocks are 24 h timing devices that phase cellular responses, co-ordinate growth, physiology and metabolism and anticipate the day-night cycle. Here we report sensitivity of the Arabidopsis thaliana circadian oscillator to sucrose, providing evidence that plant metabolism can regulate circadian function. We found that the Arabidopsis circadian system is particularly sensitive to sucrose in the dark. These data suggest that there is a feedback between the molecular components that comprise the circadian oscillator and plant metabolism, with the circadian clock both regulating and being regulated by metabolism. We used also simulations within a three loop mathematical model of the Arabidopsis circadian oscillator to identify components of the circadian clock sensitive to sucrose. The mathematical studies identified GIGANTEA as being associated with sucrose-sensing. Experimental validation of this prediction demonstrated that GI is required for the full response of the circadian clock to sucrose. We demonstrate that GI acts as part of the sucrose-signaling network and propose this permits metabolic input into circadian timing in Arabidopsis.